Performance and emission of homogeneous charge compression ignition engine with modified volume of displacements using kerosene fuel - Ahsanul, Kaiser (2014)
Homogenous Charge Compression Ignition (HCCI) is a promising combustion process which has lower fuel consumption and emits very low nitrogen oxides (NOx). It is one of the few solutions on hand that looks very promising to address the issues on the atmospheric air pollution and depleting fossil fuel resources exacerbated by increasing energy consumption of the world. However, currently there is no established means for increasing the limited power at HCCI mode. In this project, intake air heating with increasing volume of displacement were the chosen parameter that can help the combustion process of the engine to run under HCCI mode. The studies were carried out on a single cylinder air-cooled spark ignition (SI) engine. All the data analysed for the notification of performance and emission characteristics of the engine at SI condition were analysed. An experimental works have been done by fitting an intake air heater to the engine and operate the engine using kerosene fuel in HCCI mode at standard condition. Compressed auto- ignition combustion of homogeneously premixed charge of kerosene was achieved by heating the intake air. Other experiment done was to investigate the effect of volume of displacement changes of the engine cylinder diameter from 5.0cm to 5.15cm. All experiments were repeated at different engine speeds ranging from 800 to 1350 rpm to get the output parameters such as load, torque, power, volumetric efficiency, brake mean effective pressure (BMEP), exhaust gas temperatures and also NOx, carbon monoxide (CO), hydro carbon (HC) were observed at three different throttle positions with fixed speed of 800 rpm. From the study it is found that the power rate for HCCI after modification of volume displacement is 12 % - 76.5% and 1.5% - 5.6% higher than the values of HCCI using standard volume displacement and SI system respectively. Also it is found that the rate of NOx of HCCI after modification of volume displacement is 10%-12% lower than HCCI using standard volume displacement also 85%-86.5% lower than SI system.